Investigating social and environmental predictors of natal dispersal in a cooperative breeding bird. (27th February 2020) - Suh, Young Ha; Pesendorfer, Mario B; Tringali, Angela; Bowman, Reed; Fitzpatrick, John W
Abstract: Natal dispersal is a crucial life-history trait that affects both individual fitness and population structure, yet drivers of variation in dispersal probability and distance are difficult to study in wild populations. In cooperatively breeding species, individuals typically delay dispersal beyond their first breeding season and remain on the natal territory as nonbreeders, which prolongs social dynamics that can affect dispersal decisions. Using a 35-year data set covering almost 600 dispersal events in the cooperatively breeding Florida scrub-jay ( Aphelocoma coerulescens ), we examined the environmental and social parameters that predict dispersal probability over time and distance. In both sexes, dispersal probability increased with age, which, in turn, was negatively correlated with dispersal distance. In males, individuals occupying low-quality natal territories and living with a stepfather had an increased probability of dispersal. Older and more dominant males were more likely to inherit their natal territory. In females, which generally disperse earlier and farther than males, socially subordinate jays dispersed farther than dominant ones. Overall, jays that delayed dispersal the longest were more likely to attain breeding status near their natal territory, which was previously found to be associated with increased survival and lifetime fitness. Our results suggest that social dynamics and environmental factors on the natal territory affect delayed dispersal patterns differently for the two sexes in this cooperative breeder. Abstract : Social and environmental factors influence dispersal patterns in cooperatively breeding species. In Florida scrub jays, nonbreeders are more likely to disperse when older, but males from low-quality natal territories tend to disperse earlier and farther. Younger dispersers and low-ranking females move longer distances, which is associated with reduced lifetime fitness.